An integrated methodology using neutrosophic CODAS & fuzzy inference system: Assessment of livability index of urban districts - Karasan, Ali; Boltürk, Eda; Kahraman, Cengiz (SAGE Publications, 2019)
Neutrosphic sets define the uncertainty with three parameters, namely truthiness, indeterminacy and falsity. COmbinative Distance-based ASsessment (CODAS) method computes the Euclidean as the primary measure and Hamming distances as the secondary measure to assess alternatives based on predetermined criteria. In this paper, CODAS method is extended to its interval-valued neutrosophic CODAS version for handling the vagueness and impreciseness in human thoughts. A fuzzy inference system can be used as a decision making process of mapping from a given input to an output using fuzzy logic. The inputs of the used ordinary fuzzy Mamdani type inference system are crisp while the rules are fuzzy. The applicability of the proposed methodology is illustrated through the assessment of livability index of urban districts. Sensitivity analysis demonstrates the robustness of the decision-making methodology.